Resilience Based on Community-Oriented Capacities in Crisis Conditions - Mohammad Jalali; Mahdi Mahmoodzadeh Vashan; Nour Mohammad Yaghoubi; Mohammad Mohammadi (پژوهش‌های مدیریت عمومی)
AbstractIn recent years, the emphasis on community-oriented capacities as one of the important approaches to the resilience of societies in crisis conditions has attracted the attention of many experts and researchers. Therefore, the present research was conducted with the aim of identifying factors affecting resilience based on community-oriented capacities in crisis conditions and providing a model in this field using the meta-synthesis method.IntroductionToday, societies have been exposed to different types of crises, each of which has brought unfortunate consequences to societies, including threats to human health and security, destruction of resources and biological facilities, and people's activity centers (Sajadi, 2019). Therefore, nowadays, mainly the view that exists towards crisis management is to increase "resilience" in the face of various crises (Rafieiyan et al., 2011). On the other hand, experiences from crisis management in different societies show that governments alone are not able to increase the resilience of societies in crisis situations, and individual and group participation in these situations is mandatory and very effective in increasing their resilience. On the other hand, experiences from crisis management in different societies show that governments alone are not able to increase the resilience of societies in crisis situations, and individual and group participation in these situations is mandatory and very effective in increasing their resilience. (Motahari & Rafieiyan, 2016). Therefore, strategies to increase the resilience of societies are changing. In this change and evolution of the view towards resilience, the "state-oriented" and "centralist" view, which tries to formulate and implement strategies from the top down, has been replaced by a "community-oriented" view that relies on attracting participation. public and social data (Ghorbani et al., 2017). But in Iran, the evidence indicates that this change of approach and outlook has not yet happened in the country, and currently the government-oriented approach is trying to formulate and implement centralized and downward strategies to increase resilience in crisis situations. In addition, few studies have been conducted in the field of identifying and explaining factors affecting resilience based on community-oriented capacities in crisis conditions in our country; So far, a comprehensive model has not been presented as a road map for the country's crisis management managers. Therefore, the current research seeks to identify the factors affecting resilience based on community-oriented capacities in crisis situations using the meta-synthesis method and finally presenting a model in this field.Case studyThe statistical population of this research includes all articles published in domestic and foreign scientific databases between 2000 and 2023, and finally 56 studies that were closely related to the subject under study were selected as a sample.Materials and Methods The research is of an applied type with an exploratory nature, in order to collect data, a meta-synthesis method was used. The analysis of the texts was also done based on the content analysis and the dimensions and codes of the desired pattern were extracted.Discussion and ResultsBased on the analyzes carried out with the help of content analysis method on the 56 final selected researches, a total number of 3 categories, 18 concepts and 66 indicators as effective factors on resilience based on community-oriented capacities in crisis conditions were discovered in this research. and were tagged.ConclusionAccording to the studies conducted in this field and also according to the extraction of 66 indicators through the application of meta-synthesis method, it was determined that the effective factors to increase resilience in crisis situations, which are based on community-oriented capacities, are in three categories of organizational factors. , group factors and individual factors are placed, and the use of these factors in the country's crisis conditions can provide a suitable basis for reducing the incidence of negative consequences caused by it. Further, the findings of the research showed that 7 components of the institutional platform, institutional governance, institutional performance, financial and physical resource management, human resource management and information management in the form of organizational factors; 6 components of common valuation, social infrastructure, collective action and participation, social capital, acculturation and social cohesion in the form of group factors; And 5 components of knowledge, skill, awareness, attitude and capacity and ability in the form of individual factors formed the foundations of the model of factors affecting resilience based on community-oriented capacities in crisis conditions.